Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{5}{9}x\frac{4}{7}+\frac{5}{9}x\frac{3}{7}\)
\(=\frac{5}{9}x\left(\frac{4}{7}+\frac{3}{7}\right)\)
\(=\frac{5}{9}x1\)
\(=\frac{5}{9}\)
a: \(=\dfrac{3}{5}+\dfrac{2}{7}=\dfrac{21+10}{35}=\dfrac{31}{35}\)
b: \(=\dfrac{6}{5}+\dfrac{3}{2}\cdot\dfrac{1}{3}=\dfrac{6}{5}+\dfrac{1}{2}=\dfrac{12+5}{10}=\dfrac{17}{10}\)
c: \(=\dfrac{5\cdot3}{9}=\dfrac{5}{3}\)
d: =5-2/3*6/5
=5-12/15
=5-4/5
=21/5
\(\frac{7}{9}\times\frac{3}{5}+\frac{3}{5}\times\frac{5}{6}+\frac{3}{5}\times1\)
\(=\frac{3}{5}\times\left(\frac{7}{9}+\frac{5}{6}+1\right)\)
\(=\frac{3}{5}\times\frac{47}{18}\)
\(=\frac{47}{30}\)
#hoktot<3#
9x6=54
9x5=45
9x4=36
9x3=27
9x2=18
9x1=9
k mình nhé chúc năm mới vui vẻ ^.^
\(\dfrac{19}{20}-y=\dfrac{8}{5}-\dfrac{3}{4}\)
\(\Leftrightarrow\dfrac{19}{20}-y=\dfrac{32-15}{20}\)
\(\Leftrightarrow\dfrac{19}{20}-y=\dfrac{17}{20}\Leftrightarrow y=\dfrac{19}{20}-\dfrac{17}{20}=\dfrac{2}{20}=\dfrac{1}{10}\)
\(y:\dfrac{2}{3}=\dfrac{4}{9}.3\)
\(\Leftrightarrow y:\dfrac{2}{3}=\dfrac{12}{9}\Leftrightarrow y=\dfrac{12}{9}.\dfrac{2}{3}=\dfrac{8}{9}\)
\(a.\dfrac{19}{20}-y=\dfrac{17}{20}\)
\(y=\dfrac{2}{17}\)
\(b.y:\dfrac{2}{3}=\dfrac{4}{3}\)
\(y=\dfrac{8}{9}\)
a)2/5+3/10-1/2=7/10-1/2=2/10=1/5
b)8/11+8/33x3/4=8/11+2/11=10/11
c)7/9x3/14:5/8=1/6:5/8=8/30+4/15
d)5/12-7/32:21/16=5/12-1/6=3/12
nha
a) 2/5+3/10-1/2
= 4/10+3/10-5/10
= 2/10 = 1/5
b) 8/11+8/33x3/4
= 8/11+2/11
= 10/11
c) 7/9x3/14:5/8
= 1/6:5/8
= 1/6x8/5
=4/15
d) 5/12-7/32:21/16
= 5/12-7/32x16/21
= 5/12-1/6
= 5/12-2/12
= 3/12
9x3=27
= 27 nha bạn